EVOLUSI IJTIHAD IMAM SYAFI’I : Dari Qawl Qadīm ke Qawl Jadīd - Yaqin, Ainol (Al-Ahkam, 2016)
This article describes Imam al-ShÄfi'i thought in building istinbath Islamic law method and its decition's which evolved from qawl qadÄ«m to qawl jadÄ«d. He is known as the founder of uá¹£Å«l al-fiqh science which is arranged systematically-logically and critically. He tried to combine the two schools of thought, those are: Maliki, known as ahl al-á¸¥adÄ«th that thrives in the Hijaz, and the Hanafi, known as ahl al-ra'y that is entrenched in Iraq. He managed to combine the two schools by taking method good ahl al-á¸¥adÄ«th and leaving the less ones successfully. Reciprocally, he took the good ahl al-raâ€™y method and left the poor. It was done for the reason that he had studied with Imam Malik and Muá¸¥ammad ibn á¸¤asan al-Shaibani, the adherents of the Hanafi schools. The fatwa which he formulated at his living in Iraq is known as qawl qadÄ«m. After he reviewed the fatwa built in Iraq and found the fragility of the arguments as a fundamental, finally, he triggered a new law, namely qawl jadÄ«d which was based on the strong arguments.